Electrocoalescence kinetics of binary droplets in a viscous fluid. (12th October 2020) - Yin, Haoran; Luo, Xiaoming; Xu, Ke; Yan, Haipeng; He, Limin
Graphical abstract: Highlights: Evolution of droplet approach can be described by Re = 60Ca/Oh 2 . A more precise equation for droplet approach is proposed. Evolution of bridge expansion for different regimes are determined. Abstract: The electrocoalescence of droplets in a viscous fluid is resisted by viscous and inertial forces. In this paper, the effects of these forces on the droplet approaching and liquid bridge expansion are investigated. The results show that the approaching of droplets can be described by the equation Re = 60Ca/Oh 2 . In addition, we propose a modified equation for the approaching of droplets, which is in better agreement with experimental data. In the initial stage of liquid bridge expansion, the dimensionless number Oh is used to identify different regimes, which is collapsed into a unified expression by using a characteristic time. In this way, evolution of the liquid bridge in different regimes is described. Moreover, it is found that larger liquid bridge width in the viscous regime can result in a slower expansion in the later stage. This study deepens the understanding of the kinetics of droplet electrocoalescence.